Determinants of Gen Z’s Preference for Illegal Streaming Platforms: Evidence from Financial, Security, Accessibility, and Social Environment - Suci Ananda Dewi; Siti Aisyah; Aqwa Naser Daulay (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study aims to analyze the factors influencing Generation Z’s preference for illegal streaming platforms by examining financial, security, accessibility, and social environment within a digital environment. A quantitative approach was applied using structured questionnaires distributed to individuals with experience in accessing illegal streaming services. The results indicate that financial, accessibility, and social environment have a positive influence on user preferences, highlighting the importance of affordability, ease of use, and strong social exposure in shaping consumption behavior. In contrast to traditional assumptions, security does not discourage usage but instead shows a positive effect, suggesting that perceived risks are increasingly normalized among users. This indicates that repeated exposure and familiarity reduce concerns over potential threats. The study concludes that the preference for illegal streaming platforms reflects a rational decision-making process based on perceived benefits rather than ethical considerations. These findings provide practical insights for service providers and policymakers to develop more competitive, accessible, and user-centered strategies to address the growing appeal of illegal streaming platforms.